Is the effect of menu energy labelling on consumer behaviour equitable? A pooled analysis of twelve randomized control experiments. (1st March 2023) - Robinson, Eric; Boyland, Emma; Christiansen, Paul; Haynos, Ann F.; Jones, Andrew; Masic, Una; Robertson, Deirdre; Tapper, Katy; Marty, Lucile
Abstract: Menu energy labelling has been implemented as a public health policy to promote healthier dietary choices and reduce obesity. However, it is unclear whether the influence energy labelling has on consumer behaviour differs based on individuals' demographics or characteristics and may therefore produce inequalities in diet. Data were analysed from 12 randomized control trials (N = 8508) evaluating the effect of food and drink energy labelling (vs. labelling absent) on total energy content of food and drink selections (predominantly hypothetical) in European and US adults. Analyses examined the moderating effects of participant age, sex, ethnicity/race, education, household income, body mass index, dieting status, food choice motives and current hunger on total energy content of selections. Energy labelling was associated with a small reduction (f 2  = 0.004, −50 kcal, p < 0.001) in total energy selected compared to the absence of energy labelling. Participants who were female, younger, white, university educated, of a higher income status, dieting, motivated by health and weight control when making food choices, and less hungry, tended to select menu items of lower energy content. However, there was no evidence that the effect of energy labelling on the amount of energy selected was moderated by any of the participants' demographics or characteristics. Energy labelling was associated with a small reduction in energy content of food selections and this effect was similar across a range of participants' demographics and characteristics. These preliminary findings suggest that energy labelling policies may not widen existing inequalities in diet.